The applicability of disintegration tests for cohesive organic soils - Große, Anne-Katrin; Cantré, Stefan; Saathoff, Fokke (Journal of Environmental Engineering and Landscape Management, 2015)
The use of ripened fine-grained organic dredged materials as construction materials, e.g. as top soil on slopes such as landfills or dikes, is an important contribution to environmental engineering science. The materials are legally considered a waste and need to be beneficially re-used. Therefore, not only standard geotechnical parameter shave to be determined but also their erosion resistance which is a particularly critical environmental parameter. There is a variety of different tests to determine the flow dependent erosion resistance of soils, such as the erosion function apparatus (Briaud et al. 2001). In this study, however, the focus lays on the aggregate stability as an indicator for the erosion resistance under static loading, which can be determined using wet sieving and disintegration tests. The disintegration tests after Weißmann (2003) and Endell (RPW 2006) have a similar setup; however, the specific boundary conditions for the tests as well as the evaluation procedures are different. Weißmann proposed his test to determine the erosion stability of dike cover materials while the Endell test should be used for mineral sealing liners in navigation channels. In this study both tests have been used to evaluate the aggregate stability of fine-grained organic dredged materials that have been installed in large-scale research dike facilities and in the recultivation layers of different landfills. The materials showed good visual performance with respect to rainfall induced erosion so far; however, problems in determining erosion and aggregate stability indices limit the value of the studies: both disintegration tests investigated have major limitations with respect to the organic soils tested. Particularly the evaluation methods are not suitable for the soils but also some boundary conditions are critical and are discussed in this paper. The gained knowledge is a valuable basis for the development of standard characterisation methods for dredged materials in environmental and geotechnical applications.